3D customized triboelectric nanogenerator with high performance achieved via charge-trapping effect and strain-mismatching friction. (May 2022) - Kim, Young Won; Lee, Han Bit; Yoon, Jonghun; Park, Suk-Hee
Abstract: We developed a high-performance triboelectric nanogenerator (TENG) synergistically integrated with three-dimensional customized interfaces. Based on an electrospun ferroelectric poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) nanofiber mat, an interfusion with a charge-trapping layer was proposed to create an integrative negative tribo-interface component, in which a polydimethylsiloxane (PDMS) layer was partially interfused with a nanofibrous mat. The nanofiber-interfused tribo-surface notably enhanced the output performance via the charge-trapping effect, which minimized intrinsic losses in the triboelectric charges. The overall device, targeted for use in shoe insoles, was ergonomically designed based on foot geometry and fabricated accordingly via 3D printing using flexible and rigid materials. The conformal 3D customized interface provided wear comfort, even tribo-contact per foot pressure, and more importantly, augmented tribo-effect from strain-mismatching friction. Through the strain difference between the flexible and rigid parts at the contacting interface, the tribo-interface can generate additional lateral frictions as it is squeezed during foot stepping. As a result, the 3D customized TENG generated a significantly high output voltage and current of 880 V and 3.75 mA, respectively. In addition, durability of the TENG was experimentally confirmed based on at least 1500 cycles of foot stepping, in which high output performance was also sustained. The results of this study are expected to provide insights for the practical design and fabrication of 3D customized TENG systems. Graphical Abstract: This paper proposed high-performance triboelectric nanogenerator incorporating the new type of charge-trapping layer and strain-mismatching structure which takes advantages of the triboelectric performance, interactive wearable device, and great durability. ga1 Highlights: 3D scanning, modeling, and printing were used to fabricate 3D customized device. 3D wearable device was designed and customized for ergonomic wear comfort. Electrospun nanofiber mat boosts triboelectric performance via ferroelectricity. Nanofiber-interfused PDMS enhances triboelectric performance via charge trapping. Strain-mismatching friction augments triboelectricity with a sustainable performance.